Pengaruh Jumlah Uang Beredar Terhadap Profitabilitas Bank Syariah Di Indonesia Tahun 2011-2021 - Binti Koniah; Dhiyah Shabnatul Lisan; Fatiyatul Munawaroh; Agus Eko Sujianto (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study was structured to analyze the effect of the Amount of Money in Circulation (JUB) on the profitability of Islamic banks, when viewed from the variable Return On Assets (ROA). The research method uses quantitative methods with descriptive research types. The data source of this study is secondary time series data taken from financial reports published by the Financial Services Authority. The data analysis technique uses simple linear regression analysis which has previously been carried out by classical assumption tests which include the normality test and heteroscedasticity test. The results of a simple linear regression test based on the value of the regression coefficient are negative, it means that JUB (X) has a negative effect on ROA (Y).